Prevalence and Morphological Identification of Eimeria Species on Bali Cattle in Sumbawa District, West Nusa Tenggara - Pradana, Munawer; Kurniawan, Muhammad Ahdi’; Berliana, Erprinanda Galuh; ‘Ilmi, Laily Ulya Nurul; Haddar, Mariyam Al; Dharmawibawa, Iwan Doddy (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to determine the prevalence and morphological identification of Eimeria spp. from Bali cattle feces on traditional farms in Sumbawa District. A total of 300 samples were identified and 238 samples were positive, resulting in a prevalence of Eimeria spp. of 79.33%. Based on age category, the highest prevalence of Eimeria spp. was found in cattle aged 6 months-2 years (88.76%; 79/89), followed by cattle aged Â <6 months (88%; 88/100) and the lowest prevalence in cattle aged >2 years (63.96%; 71/111). Female Bali cattle had the highest prevalence of Eimeria spp. (80.55%; 145/180) than male Bali cattle (77.50%; 93/120). Based on livestock systems, the highest prevalence of Eimeria spp. was found in semi-intensive (89.15%; 74/83), then extensive (80.76%; 105/130) and the lowest in intensive (67.81%; 59/87). Six different Eimeria species were identified: E. bovis (33.19%), E. auburnensis (21.42%), E. zuernii (15.96%), E. alabamensis (12.18%), E. ellipsoidalis (10.50%), and E. canadensis (6.72%). Preventing and controlling coccidiosis infection in cattle can be done with good hygiene management.